2003
DOI: 10.4269/ajtmh.2003.68.177
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association Between House Characteristics and Malaria Vectors in Sri Lanka

Abstract: The objective of this study was to determine whether house characteristics could be used to further refine the residual insecticide-spraying program in Sri Lanka. Indoor-resting mosquito densities were estimated in 473 houses based on fortnightly collections over a two-and-a-half-year period. The type of house construction and the exact location of all houses were determined. In a multivariate analysis, distance of less than 750 meters between a house and the main vector-breeding site was strongly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 10 publications
5
47
0
2
Order By: Relevance
“…(Girls and women in Yemen -a predominantly Muslim country -are expected to keep their legs and arms covered.) Poorly constructed housing and the wearing of clothes that leave most of each arm and leg exposed have been previously identified as significant risk factors for malaria in studies in Yemen (AlTaiar et al, 2006) and Sri Lanka (Konradsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(Girls and women in Yemen -a predominantly Muslim country -are expected to keep their legs and arms covered.) Poorly constructed housing and the wearing of clothes that leave most of each arm and leg exposed have been previously identified as significant risk factors for malaria in studies in Yemen (AlTaiar et al, 2006) and Sri Lanka (Konradsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Africa and Asia have found signifi cantly higher densities of the malaria vector, the Anopheles mosquitoes, in the types of houses that poorer families tend to live in, that is, those with open eaves and windows, with walls of mud rather than brick, with a roof of thatch rather than tile or metal, and without a ceiling. 1,36,41,47,55,73 House location is also a risk factor: higher mosquito densities have been found in houses near to breeding sites 61 and in houses around the periphery of villages, where the poorest families tend to live. 57 Summing up, children from poor households are at consistently higher risk of being exposed to inadequate water and sanitation, crowding, and indoor pollution than are children from wealthy families.…”
Section: Differential Exposurementioning
confidence: 99%
“…4,5,[8][9][10][11] Several studies classify housing structures into quality groupings according to the composition of the construction materials have found poor house quality to be associated with greater presence of mosquitoes in the home and higher malaria incidence. 12,13 We recently completed a randomized control trial of malaria chemoprevention in a cohort of 600 children from different households followed from 6 months to 2 years of age in a rural area of Uganda where malaria is highly endemic.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Sri Lanka identified poor housing construction-defined as lacking brick walls and a roof of either tiles, corrugated iron, or asbestosas being associated with a higher vector density. 12 A similar study from Sri Lanka concluded that living in the worst type of house construction (mud or thatched walls and thatched roofs) was associated with a higher incidence of malaria compared with those living in houses with completed brick and plaster walls and tiled roofs. 13 In a larger study of intermittent preventive treatment of malaria conducted in Tanzania, high-quality housing based on an index of dwelling characteristics was associated with a lower incidence of malaria and vector density.…”
mentioning
confidence: 96%